2023
DOI: 10.3390/tropicalmed8080400
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Designed Sandwich ELISA for the Detection of Echinococcus granulosus Antigen in Camels for Diagnosis of Cystic Echinococcosis

Abstract: Echinococcus spp. are important cosmopolitan zoonotic parasitic tapeworms that cause a disease called hydatidosis or cystic echinococcosis (CE), which has remarkable economic losses. The objective of our study was to develop a specific IgG polyclonal antigen-based ELISA (Sandwich ELISA; capture ELISA) method for the detection of circulating Echinococcus granulosus (E. granulosus) antigens in camels infected with hydatid cysts before slaughtering and its application in serodiagnosis of CE in animals to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…Results of protoscolices viability showed that about 97% were viable with arranged hooks, uniform tegument and visible rostellum and calcareous bodies. Similar observations were recorded by Toaleb et al 37 , Barabadi et al 52 and Fateh et al 53 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results of protoscolices viability showed that about 97% were viable with arranged hooks, uniform tegument and visible rostellum and calcareous bodies. Similar observations were recorded by Toaleb et al 37 , Barabadi et al 52 and Fateh et al 53 .…”
Section: Discussionsupporting
confidence: 89%
“…We used the E. granulosus sensu lato G6 (GenBank: OQ443068.1) previously isolated from livers of naturally infected camels slaughtered at Nahia abattoir, Giza (29° 58′ 27.00″ N, 31° 08′ 2.21″ E), Egypt, and identified using NADH dehydrogenase subunit 1 (NAD1) gene by PCR 37 .…”
Section: Methodsmentioning
confidence: 99%
“…Public and animal health surveillance rely on CE diagnosis on serological assays to support image techniques. These tests, particularly ELISAs and IB, can detect E. granulosus antibodies [ 46 ]. In large-scale surveillance efforts, ELISA is often used to detect specific antibodies, which help estimate infection prevalence and identify asymptomatic patients [ 30 ].…”
Section: Methods For Diagnosis Of Cystic Echinococcosis In Intermedia...mentioning
confidence: 99%
“…Alternatively, an IgG polyclonal antigen-based ELISA was developed to detect circulatory E. granulosus antigens in camels affected with CE, using hydatid cyst germinal layer antigen (GlAg) [ 46 ]. A specific antibody polyclonal antigen sandwich ELISA method was developed to detect E. granulosus antigens circulating in camels with hydatid cysts before slaughtering, and its applicability to serodiagnosis of cystic echinococcosis in animals was also examined.…”
Section: Methods For Diagnosis Of Cystic Echinococcosis In Intermedia...mentioning
confidence: 99%
See 1 more Smart Citation